Inlier modeling for multimedia data analysis - KOKARAM, ANIL CHRISTOPHER (My University, 2004)
This paper presents a robust method to estimate the unknown standard deviation of a centred normal distribution from a mixture density. This method is applied to different signal processing problems. The first one concerns silence segmentation from audio data. The second application deals with colour class parameter extraction. In this later case, the mean is also estimated from the observations.
PUBLISHED
Keywords: Electronic & Electrical Engineering